Proceedings of the 10th International Workshop on Semantic Evaluation (SemEval-2016) 2016
DOI: 10.18653/v1/s16-1089
|View full text |Cite
|
Sign up to set email alerts
|

UWB at SemEval-2016 Task 1: Semantic Textual Similarity using Lexical, Syntactic, and Semantic Information

Abstract: We present our UWB system for Semantic Textual Similarity (STS) task at SemEval 2016. Given two sentences, the system estimates the degree of their semantic similarity. We use state-of-the-art algorithms for the meaning representation and combine them with the best performing approaches to STS from previous years. These methods benefit from various sources of information, such as lexical, syntactic, and semantic. In the monolingual task, our system achieve mean Pearson correlation 75.7% compared with human ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 17 publications
0
54
1
Order By: Relevance
“…CompiLIG The best Spanish-English performance on SNLI sentences was achieved by CompiLIG using features including: cross-lingual conceptual similarity using DBNary (Serasset, 2015), cross-language MultiVec word embeddings (Berard et al, 2016), and Brychcin and Svoboda (2016)'s improvements to Sultan et al (2015)'s method. (Nagoudi et al, 2017) Using only weighted word embeddings, LIM-LIG took second place on Arabic.…”
Section: Methodsmentioning
confidence: 99%
“…CompiLIG The best Spanish-English performance on SNLI sentences was achieved by CompiLIG using features including: cross-lingual conceptual similarity using DBNary (Serasset, 2015), cross-language MultiVec word embeddings (Berard et al, 2016), and Brychcin and Svoboda (2016)'s improvements to Sultan et al (2015)'s method. (Nagoudi et al, 2017) Using only weighted word embeddings, LIM-LIG took second place on Arabic.…”
Section: Methodsmentioning
confidence: 99%
“…We trained the word vectors on data from MediaGist gathered during the last 17 month (approximately 1M comments for each language). Brychcín and Svoboda (2016) showed that this approach leads to very good sentence representation.…”
Section: Flames Detectormentioning
confidence: 99%
“…Most of the submissions relied on a machine translation step followed by a monolingual semantic similarity, but 4 teams tried to use learned vector representations (on words or sentences) combined with machine translation confidence (for instance the submission of Lo et al (2016) or Ataman et al (2016)). The method that achieved the best performance (Brychcin and Svoboda, 2016) was a supervised system built on a word alignment-based method proposed by Sultan et al (2015). This very recent method is, however, not evaluated in this paper.…”
Section: Mt-based Modelsmentioning
confidence: 99%